The Correlation of the Open Dry Treatment to Umbilical Cord Separation Time on Newborns - Devira Natalia; Eny Sendra; Afnani Toyibah; Lumastari Ajeng Wijayanti; Arika Indah Setyarini (Journal of Ners and Midwifery, 2022)
According to East Java health profile (2019), the number of neonatal tetanus is 10 cases because of inappropriate treatment. Thus, bacteria enter the body and prolong the umbilical cord separation time. WHO (2010) and Ministry of Health Republic of Indonesia (2015) recommend umbilical cord care using an open dry method. This study attempts to identify the correlation of the open dry treatment to umbilical cord separation time according to literary results. Literature review was used to analyze the data from three online databases: PubMed, Google Scholar, and DOAJ using inclusion-exclusion criteria. The keywords were â€œUmbilical Dry Cord Care,â€â€œDay of Release of the Umbilical Cord,â€ â€œPerawatanTali Pusat Kering Terbuka,â€ and â€œLama PelepasanTali Pusat.â€ The analysis method was compared and contrast. Based on 16 articles, the results showed three categories of umbilical cord separation time by using the open dry method. Four articles indicated the fast category (< 5 days), other ten as normal (5-7 days), and the other two the slow category (> 7 days). The accurate method for the umbilical cord care is open dry because the separation time is the fastest. However, further research using primary data is needed.